Gene Expression Profiling of the Sciatic Nerve in Streptozotocin-Induced Diabetic Rats with Peripheral Neuropathy - Yiji Tu; Zenggan Chen; Feng Zhang; Zhenglin Di; Junhui Zhang; Li Cai (Journal of Diabetes Research)
Aims. To investigate the candidate biomarkers and molecular mechanisms involved in the early phase of experimental diabetic peripheral neuropathy (DPN). Methods. Diabetes in Sprague-Dawley rats was induced with streptozotocin (STZ) treatment, followed with neurological tests and histological examinations to assess the neuropathic symptoms of DPN. Microarray was performed on the sciatic nerve tissues from control rats and DPN rats at then6th week after diabetes induction, and differentially expressed genes (DEGs) between them were identified and applied for further bioinformatic analyses. Results. Experimental DPN rats were successfully constructed, presenting significantly decreased withdrawal threshold and motor nerve conduction velocity, and typical histological changes in the sciatic nerve. 597 DEGs (186 up- and 411 downregulated) were identified in DPN rats. DEGs from the 3 most highly connected clusters in the protein-protein interaction network were enriched for biological processes or pathways such as “cell division,” “cell cycle,” “protein phosphorylation,” “chemokine signaling pathway,” “neuropeptide signaling pathway,” “response to drug,” “cellular response to insulin stimulus,” “PPAR signaling pathway,” and “glycerophospholipid metabolism.” Thirteen genes were identified as the hub DEGs in the PPI network. Eleven transcriptional factors (TFs) targeting 9 of the 13 hub DEGs were predicted. Conclusions. The present study identified a pool of candidate biomarkers such as Cdk1, C3, Mapk12, Agt, Adipoq, Cxcl2, and Mmp9 and molecular mechanisms which may be involved in the early phase of experimental DPN. The findings provide clues for exploring new strategies for the early diagnosis and treatment of DPN.